Targeted molecular imaging of vascular inflammation in cardiovascular disease using nano- and micro-sized agents. - McAteer, M; Choudhury, R (2013)
Molecular imaging is emerging as a key experimental tool for the identification of inflammatory cellular and molecular processes involved in the development of cardiovascular disease. This review summarises current molecular imaging approaches for the detection of vascular inflammation using a range of nano- and micro-sized contrast agents. We highlight strategies for detection of cell adhesion molecules, which are key regulators of endothelial activation and leukocyte recruitment in atherogenesis and ischaemia-reperfusion in jury. In particular, we address the properties of targeted microparticles of iron oxide (MPIO) for MRI detection of endothelial cell-specific activation of adhesion molecules in experimental models of atherosclerosis, acute vascular inflammation and ischaemia-reperfusion injury, which are otherwise undetectable by conventional imaging modalities. The ability of targeted MPIO to detect endothelial activation could enable early subclinical disease detection and development of novel therapeutic strategies. We discuss opportunities for further development and potential translation of targeted MPIO for clinical imaging of cardiovascular disease.